Trends of Water, Sanitation, and Hygiene (WASH) Research in Indonesia: A Systematic Review - Satriani, S; Ilma, Izana Saffana; D, Daniel (Frontiers Media S.A., 2022)
This study provides an overview of water, sanitation, and hygiene (WASH) research trends in Indonesia from 1975 until April 2021. The systematic review compiled 272 articles related to the Sustainable Development Goals 6.1 and 6.2 in Indonesia, which were published in the Web of Science and Scopus databases. The results showed that the water-related topic (41%) was discussed more often than sanitation (22%) or hygiene (13%). Furthermore, the social theme (39%) was dominantly found in all these articles, mostly finding determinants of WASH-related behavior. However, few WASH implementation studies or behavioral change interventions were recorded in Indonesia, suggesting a gap between science and policy or implementation. On the other hand, hygiene-related topics (14%) and WASH-related financial themes (6%) were the least studied in Indonesia. Combinations of topics (23%) and themes (15%) were also often conducted in Indonesia, suggesting that WASH researchers started to recognize the need to analyze WASH problems holistically, i.e., from multiple perspectives. In addition, the distribution of WASH research was still dominated in the central part of Indonesia, whereas the WASH-related problems, i.e., poor WASH services, and behavior, often occur in this area. This study also offers some research gaps, both in terms of topics, themes, and regional distribution, that need to be considered for the design of future WASH research in Indonesi